The Effect of Ethical Leadership on Bribing and Favoritism: A Field Research Study. (4th May 2019) - Asencio, Hugo D.
Abstract : Corruption has many negative consequences for democratic society. Despite the widespread development and implementation of legal and administrative mechanisms to fight it, corruption persists in American government. This underscores the need for ethical leadership in public agencies. Nevertheless, despite the potential benefits of ethical leadership, empirical research on its effectiveness in reducing corruption in government organizations remains underdeveloped. The present field research study advances the public administration literature by investigating the effect of ethical leadership on bribing and favoritism. It uses survey data collected from government employees, managers, and elected officials in a U.S. state. The results indicate that ethical leadership is likely to reduce bribing and favoritism in government agencies. The findings highlight the importance of ethical leadership in the fight against corruption and the need to expand it further in public agencies.